Novel therapies targeting vascular endothelium. - Tousoulis, D; Antoniades, C; Koumallos, N; Marinou, K; Stefanadi, E; Latsios, G; Stefanadis, C (2006)
Endothelial dysfunction has been identified as a major mechanism involved in all the stages of atherogenesis. Evaluation of endothelial function seems to have a predictive role in humans, and therapeutic interventions improving nitric oxide bioavailability in the vasculature may improve the long-term outcome in healthy individuals, high-risk subjects, or patients with advanced atherosclerosis. Several therapeutic strategies are now available, targeting both the synthesis and oxidative inactivation of nitric oxide (NO) in human vasculature. Statins seem to be currently the most powerful category of these agents, improving endothelial function and decreasing cardiovascular risk after long-term administration. Other cardiovascular agents improving endothelial function in humans are angiotensin-converting enzyme inhibitors/angiotensin receptors blockers, which increase NO bioavailability by modifying the rennin-angiotensin-aldosterone system. Newer therapeutic approaches targeting endothelial dysfunction in specific disease states include insulin sensitizers, L-arginine (the substrate for endothelial NO synthase [eNOS]) as well as substances that target eNOS "coupling," such as folates or tetrahydrobiopterin. Although there are a variety of strategies to improve NO bioavailability in human endothelium, it is still unclear whether they have any direct benefit at a clinical level.